Вирішення конфліктів у традиційному суспільстві: єднання моралі і права - Воропай, Т. С.; Voropay, T. S.; ORCID: http://orcid.org/0000-0001-6170-5512 (Форум права. - 2018. - № 1. – С.32- 35, 2018)
Запропонована морально-правова інтерпретація ситуації конфлікту, описаного у книзі відомого антрополога Д. Даймонда «Світ позавчора». Мова йде про дорожньо-транспортну пригоду, внаслідок якої загинула дитина. Здійснено порівняльний аналіз механізмів залагодження конфлікту у традиційному суспільстві (Нова Гвінея), результатом чого стає відновлення відносин, та правових процедур сучасної держави, націлених передусім на пошук і покарання винуватця. Аргументовано, що деякі аспекти традиційного вирішення конфлікту можуть бути корисними для правових відносин сьогодення.

Moral and law interpretation of the conflict, described in the D. Diamond's book «The world until yesterday: What can we learn from traditional societies?», is proposed in this paper. Traffic collision in which a child was killed is a matter of discussion. Comparative analysis between mechanisms of the conflict resolution in traditional society (New Guinea), resulted in restoration of regular mutual relations, and legal procedures in a contemporary state, focused on finding and punishing the guilty primarily, is fulfilled. It is argued, some aspects of the traditional conflict resolution may be useful in modern legal relations. The goal of resolving conflicts among members of traditional society is not finding out who is right and who is guilty only but restoring regular relationships in society where everyone knows each other and where hostility between any two members of a community undermines its stability. Like many other traditional communities, the New Guinea people live outside the effective control of state law enforcement system. They, nevertheless, can achieve justice by means their own traditional mechanism that combine some moral and legal procedures organically. Although the law, at least written, does not exist here, some moral or proto-legal mechanism works. The peace process involves some «compensation» usually. Although this term is quite ambiguous, it seems impossible to «compensate» death of a child. Therefore there are especial New Guinean practice and relevant term «money of compassion», that is, money paid to prove apologizing for what happened as well as deep regret. It is pointed out, that traditional New Guinean mechanisms of justice have goals that are radically different from those pursued by the state by means of law enforcement system. Of course, it is impossible to exclude or substitute modern system of state justice in many conflict cases at the XXI century, e.g. between local people and strangers. However, some traditional mechanisms for resolving conflict situations seems both adequate and useful until now (we are currently seeing this in the so-called restorative justice too).

Предложена морально-правовая интерпретация конфликта, описанного в книге известного антрополога Д. Даймонда «Мир позавчера». Речь идет о дорожно-транспортном происшествии, в результате которого погиб ребенок. Осуществлен сравнительный анализ механизма урегулирования конфликта в традиционном обществе (Нова Гвинея), результатом которого является восстановление отношений, и правовых процедур современного государства, нацеленных преимущественно на поиск и наказание виновного. Аргументировано, что некоторые аспекты традиционного решения конфликта могут быть полезными в современных правовых отношениях.
Conflict Resolution in Traditional Society: Synthesis of Moral and Law
Разрешение конфликтов в традиционном обществе: соединение морали и права
Воропай, Т. С. Вирішення конфліктів у традиційному суспільстві: єднання моралі і права [Електронний ресурс] / Т. С. Воропай // Форум права. - 2018. - № 1. - С. 32–35. - Режим доступу: http://nbuv.gov.ua/jpdf/FP_index.htm_2018_1_6.pdf.
Воропай Т. С. Вирішення конфліктів у традиційному суспільстві: єднання моралі і права. Форум права: електрон. наук. фахове вид. 2018. № 1. С. 32–35. URL: http://nbuv.gov.ua/jpdf/FP_index.htm_2018_1_6.pdf.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; конфлікт; традиційне суспільство; мораль; право і мораль; конфликт; традиционное общество; право и мораль; conflict; traditional society; moral and law